Fire station location analysis in a metropolitan area. (1st January 2014) - Savsar, Mehmet
Facility location problem involves locating a facility to optimise some performance measure. Location of a public facility significantly affects its service quality. Therefore, it is essential to give special consideration in selecting a proper location for a facility that will be used to meet the community needs in metropolitan areas. Locating a fire station is an example for a service facility location for a community. The main objective in locating a fire station is to minimise the response time, which is the time duration between receiving a call and reaching the place of incident. In metropolitan areas, fire vehicles need to cross highways and other traffic obstacles through some obstacle-overcoming points which delay the response time. Therefore, in the analysis of fire station locations, obstacles have to be taken into consideration. In this paper, fire station location problem is analysed. Models are developed for the fire station location problems, which involve obstacles and obstacle-overcoming points. Particular case problems are analysed and the results are presented.